Understanding Degassing and Transport of CO2-rich Alkalic Magmas at Ross Island, Antarctica using Olivine-Hosted Melt Inclusions. (4th August 2017) - Rasmussen, Daniel J.; Kyle, Philip R.; Wallace, Paul J.; Sims, Kenneth W. W.; Gaetani, Glenn A.; Phillips, Erin H.
Abstract: Volatiles play an important role in magmatic and volcanic processes. Melt inclusions are a powerful tool to study pre-eruptive volatiles, but interpretation of their H2 O and CO2 variations can be difficult. The H2 O and CO2 contents of melt inclusions from nine basanites from Hut Point Peninsula, Mt Terror and Mt Bird on Ross Island, Antarctica, were studied to understand better the behavior of volatiles in the magmas and to provide insight into magma transport and storage processes. Ninety olivine-hosted (Fo78–-88 ) melt inclusions were examined along with the composition of the associated bulk-rock samples. The H2 O (0·4–2·0 wt %) and CO2 (0·2–0·9 wt %, or 0·2–1·8 wt % after correction for vapor bubbles) variations in the melt inclusions cannot be explained by equilibrium degassing. A strong correlation between melt inclusion radius and H2 O content for Hut Point samples indicates that diffusive loss of H + has occurred. Based on vapor saturation pressure trends, it is inferred that a magma reservoir existed below Hut Point at a depth of ∼18 km, and by modeling diffusive loss of H + for melt inclusions, it is shown that the magmas ascended from this depth in less than a year. Melt inclusions from Terror and Bird lack evidence of diffusive loss of H + and there are no strong chemical indicators of CO2 fluxing. Compositional heterogeneities in melt inclusions indicate that magma mixing occurred, making it difficult to interpret H2 O and CO2 trends. Melt inclusions from these volcanoes were entrapped polybarically, inconsistent with entrapment in a single storage region. Published analyses of 54 olivine-hosted (Fo53–83 ) melt inclusions in seven samples from Erebus volcano on Ross Island were re-examined for comparative purposes. Low H2 O (∼0·1 wt %) and CO2 (0–0·2 wt %) contents and the evolved compositions of these indicate that Erebus magmas undergo shallow (<6 km) crystallization before eruption, probably in a shallow storage region. Magmas from the surrounding volcanoes show no sign of shallow storage.